Um estudo sobre a participação infantil: o que nos dizem as pesquisas? - Soares, Lilian Maria (2022)
The present research, based on the Sociology of Childhood, starts from the premise that the child is an active social being endowed with rights and capable of effectively participating in the political, social and cultural processes that concern them. In this sense, we understand that the space built/offered in the educational environment by the adult must create opportunities for the child to experience different experiences, transforming it into a democratic place of participation, interaction, listening, dialogue and learning, as well as, in a favorable place for the formation of identity, the development of autonomy and citizen awareness. Therefore, we aim to investigate how the theme of child participation has been approached and discussed by researchers in academic-scientific publications, aiming to understand the contributions of these researches to the configuration of children's participation in the context of Early Childhood Education. The study is based on the precepts of qualitative research and as a methodological procedure, a bibliographic study was chosen, called the State of Knowledge. The data were collected from the reading of academic-scientific productions specifically mapped in the Digital Library of Theses and Dissertations (BDTD) of the Brazilian Institute of Science and Technology Information (Ibict). The construction of the data analysis was through the use of the qualitative content analysis method. The data revealed that children participate in the educational context directly or indirectly, even if they are not yet considered by adults in their actions. In this sense, the data showed that children claim participation and protagonism through their multiple languages. It was also possible to observe that the most favorable spaces for children's participation are games and conversation circles. In view of the analyses, we could see that although the participation of children exists in educational spaces, it demands a systematization of work that requires reflections and confrontations about practices, actions, organizations of times, spaces and conceptions about children and childhood. Therefore, we found that studies on child participation still lack a greater space for reflection in Brazil.